MEMBANGUN KELUARGA HARAPAN ANTI KORUPSI: Perspektif Nilai-Nilai Alqur`an - Moh Abdul Kholiq Hasan (UIN Raden Mas Said Surakarta, 2014)
The Family in the Qur'an is the main pillar of a society.Family occupies a strategic position in the formation of man. Includedin the hopes of building a family of anti-corruption. Planting the anticorruptionneeds to be done early. Particularly through the practice ofreligion is not limited to mere ritual activity. But also to transform thevalues of rituals in daily life character. Among Qurani values, whichcan be used to build the character of a family of anti-corruption is theintention of working as a worship, cultivate a sense of shame in thefamily, cultivate honesty in the family, even the simplest life as highofficials, educate the family to work hard. And the most important wayin instilling the values Qur`an is the real example of parents for theirchildren. So that when they grow up to be a part of the communitywho are able to protect themselves from a variety of crimes includingcorruption.